Modified Radial Based Neural Network for Clustering and Routing Optimal Path in Wireless Network - Hoomod, Haider Katdhum; Jebur, Tuka Kareem (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Several methods have been developed for routing problem in MANETs wireless network, because it considered very important problem in this network ,we suggested proposed method based on modified radial basis function networks RBFN and Kmean++ algorithm. The modification in RBFN for routing operation in order to find the optimal path between source and destination in MANETs clusters. Modified Radial Based Neural Network is very simple, adaptable and efficient method to increase the life time of nodes, packet delivery ratio and the throughput of the network will increase and connection become more useful because the optimal path has the best parameters from other paths including the best bitrate and best life link with minimum delays. The results show how the proposed routing algorithm produces higher speed comparing with Dijkstra algorithm and finds the optimal path in addition to shortest path. Proposed routing algorithm depends on the group of factors and parameters to select the path between two points in the wireless network.